2015
DOI: 10.1186/s13014-015-0574-6
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic MRI findings in relapsed prostate cancer after radical prostatectomy

Abstract: Purpose/ObjectiveLittle is known about the clinical impact of using multiparametric MRI to plan early salvage radiotherapy after radical prostatectomy. We aimed to evaluate the incidence and location of recurrence based on pelvic multiparametric MRI findings and to identify clinical variables predictive of positive imaging results.Materials and methodsWe defined radiological criteria of local and lymph node malignancy and reviewed records and MRI studies of 70 patients with PSA recurrence after radical prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…The sensitivity of MRI for local recurrence and pelvic lymph node metastases was 89% and 64%, respectively [9]. Hernandez et al evaluated 70 patients with a median PSA of 0.38 (range 0.00–8.05), and identified 7 (10%) of patients with nodal metastases [25]. There was no pathologic correlation for the nodal findings, and it is unclear if patients receiving ADT at the time of imaging were included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of MRI for local recurrence and pelvic lymph node metastases was 89% and 64%, respectively [9]. Hernandez et al evaluated 70 patients with a median PSA of 0.38 (range 0.00–8.05), and identified 7 (10%) of patients with nodal metastases [25]. There was no pathologic correlation for the nodal findings, and it is unclear if patients receiving ADT at the time of imaging were included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although we only found an association between PSA values at the time of biochemical failure and MRI positivity, many studies have reported an association between PSA and choline PET/CT [22]. Thus, after RP, the optimal PSA cut-off level for choline PET/CT analysis seems to be between 1 and 2 ng/mL [23], while for MRI, the corresponding value appears to range from 0.3 to 0.54 ng/mL [5]. In addition to the PSA value, several studies have reported that PSA kinetics (PSADT, PSA velocity) are strong predictors for positive PET and MRI findings, even in patients with low PSA values [4, 5, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, after RP, the optimal PSA cut-off level for choline PET/CT analysis seems to be between 1 and 2 ng/mL [23], while for MRI, the corresponding value appears to range from 0.3 to 0.54 ng/mL [5]. In addition to the PSA value, several studies have reported that PSA kinetics (PSADT, PSA velocity) are strong predictors for positive PET and MRI findings, even in patients with low PSA values [4, 5, 23]. We found that PSADT was significantly associated with the type of pelvic recurrence: patients with a higher PSADT had an increased probability of local recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations